Contribution of ITS towards identifying mites of the family Macrochelidae (Acari: Mesostigmata) collected from cattle manure in São Paulo, Brazil - Anjos, Karina A.; Araújo-Silva, Shirley B.; Fiorini, Leonardo C.; Duarte, Fernanda C.; Sampaio, Paulo H. S.; Rodrigueiro, Tatyana S. C.; Harakava, Ricardo; Mendes, Márcia C. (Zootaxa, 2020)
The aim of this study was to analyse morphological and molecular (ITS region) characteristics for eight species of mites in the family Macrochelidae that are present in cattle manure in Brazil. Six of these species were already known in Brazil and, for five of these, both tools (morphology and phylogeny) were concordant regarding all the trees used. The species G. saprophila and M. scutatus were reported in the present study for the first time in Brazil. The data obtained in this study suggest that the molecular analysis corroborated the morphological identification in most species of macrochelids. The results also demonstrate the need to correlate identifications through dichotomous keys, by using phylogenetic studies to better distinguish cryptic species.